Dental and periodontal status of 12-year-old Dai school children in Yunnan Province, China: a cross-sectional study. Issue 1 (December 2015) - Zhang, Shinan; Xu, Biao; Liu, Juan; Lo, Edward; Chu, Chun-Hung
Abstract Background The Dai people are one of the ethnic minorities in China and have a population of 1, 260, 000. They have the same origin as one of the main ethnic groups in Laos and Thailand. The study aims to describe the dental caries and gingival status of 12-year-old Dai children in China and to study the factors affecting their oral-health status. Methods This cross-sectional oral-health survey was conducted from 2011–2012 with ethics approval. A sample of 12-year-old Dai children living in Yunnan, China, was selected using a multistage and cluster sampling method. One trained examiner performed the clinical examination. Caries experience was measured using DMFT index, and gingival status was assessed with CPI index. A self-completed questionnaire was sent to the children, and they were asked about their backgrounds and oral-health-related behaviors and oral-health knowledge. Binary logistic regression analysis was performed to investigate the factors that affected the caries status. Results A total of 875 children were invited, and 823 (94 %) joined the survey. The prevalence of caries experience among the participants was 40 %. The mean DMFT and DT scores were 0.9 and 0.8, respectively. Most children (93 %) had gingivitis, and many (46 %) had calculus. Girls and those who had visited a dentist during the previous year had a higher prevalence of caries. Conclusion Dental caries were prevalent among 12-year-old Dai children in China. The periodontal condition of most of the children was poor. Caries were associated with gender and dental attendance.